PENERAPAN BALANCED SCORECARD SEBAGAI TOLOK UKUR PENGUKURAN KINERJA - Wiguna, Kusnadi Yudha; Wati, Riswati; Marliza, Yayuk (Universitas Muhammadiyah Palembang, 2019)
The purpose of this study was to determine the performance of the Dwi Sari Lubuklinggau Mother and Child Hospital measured using the Balanced Scorecard. This research is a qualitative descriptive study. The operational variable of this research is performance measurement with four perspective indicators in the balanced scorecard namely financial perspective, customer perspective, internal business process perspective, learning and growth perspective. Data sources used in this study are primary data obtained from questionnaire results for patients and hospital employees and interviews. Secondary data is in the form of hospital profiles and financial data and hospital data. The data analysis technique used is descriptive analysis. The results showed that Dwi Sari Lubuklinggau's Mother and Child Hospital so far in measuring financial performance is only based on financial reports by looking at revenue growth and has not yet implemented performance measurement with a balanced scorecard. The application of the balanced scorecard to the Dwi Sari Lubuklinggau Mother and Child Hospital using four perspectives on average shows good performance, there are only a few indicators of performance measurement on the customer's perspective and the perspective of internal business processes that show poor performance.